Polycarbonate polishing solution, preparation method and polishing solution performance testing method

By preparing a polycarbonate polishing liquid containing specific components, the problem of difficult polishing of polymer materials such as polycarbonate is solved, efficient and stable polishing effect is achieved, and the service life of the polishing liquid is extended.

CN119505710APending Publication Date: 2025-02-25JIHUA LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411684528.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively polish polymer engineering materials such as polycarbonate, and the stability and service life of the polishing liquid are insufficient.

Method used

By preparing a polycarbonate polishing liquid containing water, silica, coupling agent, oily lubricant, surfactant, organic alkali and dispersant, the particle size of silica abrasive particles is controlled and dispersed by coupling agent and dispersion The synergistic effect of the agent ensures the stability of the polishing liquid.

Benefits of technology

It realizes effective precision polishing of polymer materials such as polycarbonate, avoids surface scratches, and ensures the stability and long-term use ability of polishing liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505710A_ABST
    Figure CN119505710A_ABST
Patent Text Reader

Abstract

The invention discloses a polycarbonate polishing solution, a preparation method and a polishing performance testing method, and belongs to the technical field of polishing solutions, the polycarbonate polishing solution comprises the following components by mass: 58.5-62.5% of water, 22-26% of silica, 4-6% of a coupling agent, 3-5% of an oily lubricant, 3-5% of a surfactant, 2.5-3% of an organic alkali, and 0.5-1.0% of a dispersant; and the particle diameter of the silicon dioxide is 75-90 nm. By controlling the particle size of the silicon dioxide abrasive particles in the polishing solution, effective and precise polishing of high polymer materials such as polycarbonate can be realized; the oiliness agent, the organic base and the surface active agent are matched for use, so that the surface of the polycarbonate material can be prevented from being scratched when the polycarbonate material is polished; the synergistic effect of the coupling agent and the dispersing agent can ensure the stable storage of the polishing solution and avoid the agglomeration of the nano silicon dioxide particles in the polishing solution, so that the polishing solution can be used and recycled for a long time. The testing method provided by the invention can be used for intuitively evaluating the action effect of the polishing solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing liquids, and in particular to a polycarbonate polishing liquid, a preparation method and a polishing liquid performance testing method. Background Art

[0002] As one of the five major engineering plastics, polycarbonate has the advantages of light weight, wear resistance, easy molding and processing, long service life, as well as good heat resistance, dimensional stability, chemical stability and dielectric properties. It is widely used in automobiles, electronics and electrical, optical storage (optical disc substrate), construction and building materials, office equipment, packaging, sports equipment, medical care and other fields.

[0003] As a thermoplastic industrial plastic, polycarbonate can be manufactured into products through injection molding, extrusion, high-temperature pressing, casting, etc. However, during the injection molding process, defects such as peeling, flash, and weld marks will often appear on the edges of the workpiece. Especially for workpieces that have tolerance requirements for specific positions, or have requirements for surface roughness and brightness, the defective positions on the surface need to be further polished to ensure that the product is usable.

[0004] Polishing processes include mechanical polishing, chemical polishing, chemical-mechanical polishing, electrolytic polishing, ultrasonic polishing, magnetic grinding polishing, etc. Among them, mechanical polishing is the most traditional, but it can obtain the lowest surface roughness. Mechanical polishing relies on the grinding and rolling action of nano-scale fine polishing abrasives evenly dispersed in the polishing liquid to remove defects on the grinding surface of the sample. For polycarbonate, because of its soft texture, in order to achieve sufficient polishing effect while avoiding surface scratches, it is necessary to select abrasives of appropriate size and effective dispersion.

[0005] There are few reports on polishing liquids for polymer engineering materials such as plastics in the prior art. However, for the polishing liquid of organic glass, the Chinese patent document with the announcement number CN115305012B discloses an organic glass polishing liquid and a polishing method. The abrasive particles in the organic glass polishing liquid disclosed therein are aluminum oxide and silicon oxide with a particle size of less than 1.2 microns. The particle size and particle size range of the abrasive particles are too large to provide clear guidance. In addition, the selected emulsifier and lubricant are oily and are not easy to stably exist in the water phase of the polishing liquid.

[0006] In addition, since the polishing processing method of workpieces in actual mass production is significantly different from the development environment in the laboratory, in order to effectively evaluate the processing effect of the polishing liquid in the laboratory, it is necessary to develop a polishing performance test method for the polishing liquid that can be used in the laboratory.

[0007] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention

[0008] The purpose of the present invention is to provide a polycarbonate polishing liquid, a preparation method and a polishing liquid performance testing method, aiming to solve the problem that the existing polishing liquid is not suitable for polishing polymer engineering materials such as polycarbonate, and at the same time provide a polishing liquid polishing performance testing method that can effectively evaluate the processing effect of the polishing liquid in the laboratory.

[0009] To achieve the above object, the solution provided by the present invention is:

[0010] A polycarbonate polishing liquid, calculated by mass percentage, comprises the following components:

[0011] Water 58.5-62.5%, silicon dioxide 22-26%, coupling agent 4-6%, oily lubricant 3-5%, surfactant 3-5%, organic base 2.5-3%, dispersant 0.5-1.0%;

[0012] The silicon dioxide is obtained from silica sol, and the silica sol comprises the following components:

[0013] Silicon dioxide 45%, water 55%.

[0014] The oily lubricant includes at least one of fatty acid octyl ester, fatty acid isooctyl ester, oxidized fatty acid octyl ester, tall oil, fatty acid methyl ester, tall oil fatty acid, pentaerythritol oleate, cottonseed oil, tetrapolyricinoleate, neodecanoic acid, and trimethylolpropane oleate.

[0015] The organic base includes at least one of monoethanolamine, diethanolamine, triethanolamine, diglycolamine, tricyclohexylamine, dimethylamine, diethylamine, aniline and tetrahydroxymethylamine.

[0016] The surfactant includes at least one of lauramide propylamine oxide, tallow amine polyoxyethylene ether, oleylamine polyoxyethylene ether, dodecylamine polyoxyethylene ether, lauryl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, oleic acid polyoxyethylene ether and Tween-80.

[0017] The coupling agent includes at least one of ethanol, ethylene glycol, isopropanol, diethylene glycol, isopentyl glycol, cyclohexanol, isooctyl alcohol, Guerbet alcohol, ethylene glycol monobutyl ether, and diethylene glycol butyl ether.

[0018] The dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, sodium citrate, disodium edetate, sodium gluconate, sodium glucoheptonic acid, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium acid pyrophosphate, and disodium dihydrogen pyrophosphate.

[0019] The present invention also provides a method for preparing a polycarbonate polishing liquid, comprising the following steps:

[0020] S001. Add coupling agent and dispersant to water and stir until the solution is clear and transparent;

[0021] S002. Slowly add the oil lubricant, the organic base and the surfactant to the mixed solution obtained in step S001, and stir until the solution changes from turbid and unstable to clear and transparent uniform;

[0022] S003. Slowly add silicon dioxide to the mixed solution obtained in step S002, and stir until the solution is uniform to obtain a milky white polishing solution.

[0023] The present invention also provides a polishing liquid performance test method, which is used to test the performance of the polycarbonate polishing liquid, comprising the following steps:

[0024] C001. Cut the formed polycarbonate material into test pieces suitable for laboratory polishing machines;

[0025] C002. Use sandpapers of 180 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh and 2500 mesh, and grind and polish the test block in succession from coarse to fine sandpaper. Rinse the surface of the test block after each grinding and polishing.

[0026] C003. Prepare the polycarbonate polishing solution or a dilution containing the polycarbonate polishing solution;

[0027] C004. Place the polishing pad on the turntable of the polishing machine, drip the polishing liquid evenly on the polishing pad, and then place the test block polished with sandpaper to start polishing. The positive pressure between the test block and the polishing pad is 5N, the polishing pad speed is 400-500RPM, the test block speed is 0-150RPM, and the polishing time is 7-10min. During polishing, drip the polishing liquid continuously at the position where the polishing pad contacts the test block and is relatively close to the center. After polishing, rinse off the polishing liquid remaining on the surface with water.

[0028] C005. Observe the grinding and polishing conditions of the polished test block under a high-power optical microscope.

[0029] Furthermore, in step C003, the diluent of the polycarbonate polishing liquid includes polycarbonate polishing liquid and water, and the mass ratio of the polycarbonate polishing liquid to water is 1:(1-3).

[0030] The beneficial effects of the present invention are as follows: the present invention provides a polycarbonate polishing liquid, which can achieve effective precision polishing of high molecular materials such as polycarbonate by controlling the particle size of silica abrasive particles in the polishing liquid; the oiliness agent, organic base and surfactant are used in combination to avoid scratches on the surface of the polycarbonate material when the polycarbonate material is polished; the synergistic effect of the coupling agent and the dispersant can ensure the stable existence of the polishing liquid, avoid agglomeration of nano-silica particles in the polishing liquid, and enable the polishing liquid to be used for a long time and recycled.

[0031] The present invention also provides a method for preparing a polycarbonate polishing liquid. The provided preparation method is simple and efficient, and the equipment used in the preparation method is easy to deploy, and can be widely promoted in material processing, especially in the polymer engineering material production and processing industry.

[0032] The present invention also provides a polishing liquid performance test method. In the provided test method, by rough grinding a polycarbonate test block and strictly controlling the positive pressure between the test block and the polishing pad, the polishing pad rotation speed and the polishing time when the laboratory polishing machine is working, the polishing processing effect of the bulk production site can be reproduced, so that the processing effect of the polishing liquid in production can be effectively evaluated. The polishing performance test method of the polishing liquid provided by the present invention is simple to operate, can be performed using a variety of laboratory polishing machines and optical microscopes, and can intuitively evaluate the effect of the polishing liquid. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention provides a flow chart of a method for preparing a polycarbonate polishing liquid.

[0034] Figure 2 The present invention provides a flow chart of a method for testing the polishing performance of a polishing liquid.

[0035] Figure 3 This is a photograph of the polycarbonate material in Example 1 being polished under an ultra-depth-of-field microscope (the brown lines are the effects of light photography, not defects on the surface of the material after polishing).

[0036] Figure 4 This is a photograph of the polycarbonate material in Comparative Example 1-1 being polished under an ultra-depth-of-field microscope.

[0037] Figure 5 This is a photograph of the polycarbonate material in Comparative Example 1-2 being polished under an ultra-depth-of-field microscope.

[0038] Figure 6 The following are photos of the polycarbonate material in Comparative Examples 1-3 being polished under an ultra-depth-of-field microscope.

[0039] Figure 7 This is a photograph of the polycarbonate material in Example 2 being polished under an ultra-depth-of-field microscope.

[0040] Figure 8 This is a photograph of the polycarbonate material in Comparative Example 2-1 being polished under an ultra-depth-of-field microscope.

[0041] Fig. 9 This is a photograph of the polycarbonate material in Comparative Example 2-2 being polished under an ultra-depth-of-field microscope.

[0042] Fig.10 This is a photograph of the polycarbonate material in Example 3 being polished under an ultra-depth-of-field microscope.

[0043] Fig.11 This is a photograph of the polycarbonate material in Comparative Example 3-1 being polished under an ultra-depth-of-field microscope.

[0044] Fig.12 This is a photograph of the polycarbonate material in Comparative Example 3-2 being polished under an ultra-depth-of-field microscope. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The present invention provides a polycarbonate polishing liquid, which comprises the following components calculated by mass percentage:

[0047] Water 58.5-62.5%, silicon dioxide 22-26%, coupling agent 4-6%, oil lubricant 3-5%, surfactant 3-5%, organic base 2.5-3%, dispersant 0.5-1.0%.

[0048] In the above-mentioned polycarbonate polishing liquid, silicon dioxide is used as an abrasive, and its particle diameter is nanometer-level. The shape of nano silicon dioxide particles is close to spherical, and it can have a relatively gentle grinding effect on soft materials such as polycarbonate. The oily lubricant can be adsorbed on the contact surface of the material through polar groups to form a molecular directional adsorption film, which can further alleviate the scratches of the softer polycarbonate surface by the harder abrasive particles on the basis of effectively grinding and polishing to remove surface defects. The silicon dioxide preferably has a particle diameter of 75 to 90 nm. On the premise of achieving effective grinding and polishing of polycarbonate, it can also avoid surface scratches caused by excessive grinding and polishing, and can also avoid excessive heat generation during the grinding and polishing process, which causes orange peel texture on the surface of the polycarbonate material.

[0049] Organic alkali can adjust the pH of the polishing liquid, ensuring that the oily components (such as oily lubricants) in the polishing liquid are not contaminated by fungi, so that the polishing liquid is not easily ineffective. By introducing surfactants into the formula system of the polishing liquid, the oily lubricant can be effectively dispersed in the polishing liquid, and at the same time, the surface tension of the polishing liquid can be reduced, making it easier for the oily lubricant to form a molecular directional adsorption film on the surface of the material, thereby alleviating the scratches of the harder abrasive particles on the softer polycarbonate surface.

[0050] In addition, organic bases can react with oily lubricants to form water-soluble substances. Combined with surfactants, the oily lubricants can be effectively dispersed in the polishing liquid. During polishing, they can play a lubricating role between the silica abrasives and the polycarbonate, preventing surface scratches caused by excessive grinding and polishing.

[0051] The coupling agent can improve the compatibility of organic and inorganic components in the polishing liquid, and can also prevent problems such as machine pollution and nozzle clogging caused by the agglomeration of silica particles, ensuring the stability of the polishing liquid and the normal progress of the polishing process. In addition, the coupling agent can also enhance the lubrication of the polishing liquid, and after the polycarbonate material is polished, it can also improve the brightness of the polycarbonate surface. The dispersant can form an effective synergistic effect with the coupling agent, further ensuring that the silica particles do not agglomerate during use, and at the same time can help improve the brightness of the polycarbonate surface.

[0052] It can be seen that the present invention can achieve effective precision polishing of polymer materials such as polycarbonate by controlling the particle size of silica abrasive particles in the polishing liquid; the combination of oiliness agent, organic base and surfactant can avoid scratches on the surface of polycarbonate material during polishing; the synergistic effect of coupling agent and dispersant can ensure the stable existence of the polishing liquid, avoid agglomeration of nano-silica particles in the polishing liquid, and enable the polishing liquid to be used for a long time and recycled.

[0053] Preferably, the silicon dioxide is obtained from a silica sol (i.e., a water dispersion of nano-silicon dioxide) having a solid content of 45%, and the silica sol includes the following components: 45% silicon dioxide and 55% water. By adjusting the synthesis conditions of the silica sol, such as pH value, temperature, and reaction time, the diameter of the silicon dioxide particles can be conveniently controlled, so that the performance of the polycarbonate polishing liquid can meet the requirements of grinding and polishing. The silica sol has good compatibility with the oily components in the polishing liquid, and the silica sol is easily dispersed in the liquid and can form a stable suspension, which is very beneficial to the application of the polishing liquid.

[0054] The oily lubricant includes at least one of fatty acid octyl ester, fatty acid isooctyl ester, oxidized fatty acid octyl ester, tall oil, fatty acid methyl ester, tall oil fatty acid, pentaerythritol oleate, cottonseed oil, tetrapolyricinoleate, neodecanoic acid, and trimethylolpropane oleate.

[0055] In a preferred embodiment, the oily lubricant is a compound of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is (1-2): (2-3). Neodecanoic acid has a relatively small molecular size, and when compounded with fatty acid methyl ester having a larger molecular size, it can produce an effective synergistic effect, thereby greatly improving the lubricating performance of the polishing liquid. However, when fatty acid methyl ester and neodecanoic acid are used alone, the lubricating effect of the polishing liquid is insufficient, and when polishing the polycarbonate material, over-polishing (i.e., excessive polishing) is likely to occur, which will cause new wear marks and orange peel on the surface of the polycarbonate material.

[0056] The organic base includes at least one of monoethanolamine, diethanolamine, triethanolamine, diglycolamine, tricyclohexylamine, dimethylamine, diethylamine, aniline, and tetrahydroxymethylamine. In a preferred embodiment, the organic base is diglycolamine. The amino group in the organic base reacts with the oily lubricant to generate a water-soluble substance, and the polishing liquid itself is a water-based system. When used, it is necessary to ensure that the oily components such as the oily lubricant can be fully dispersed in water. Therefore, the generation of the water-soluble substance can assist the surfactant and enhance the dispersion effect of the oily lubricant in the polishing liquid, so that during the grinding and polishing process, the polishing liquid can form a high-strength lubricating film on the surface of the material, which can alleviate the scratches of the harder abrasive particles on the softer polycarbonate surface.

[0057] The surfactant includes at least one of lauramide propylamine oxide, tallow amine polyoxyethylene ether, oleylamine polyoxyethylene ether, dodecylamine polyoxyethylene ether, lauryl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, oleic acid polyoxyethylene ether, and Tween-80. In a preferred embodiment, the surfactant is lauryl alcohol polyoxyethylene ether, and the synergistic effect of lauryl alcohol polyoxyethylene ether and diglycolamine is the best.

[0058] The coupling agent includes at least one of ethanol, ethylene glycol, isopropanol, diethylene glycol, isopentyl glycol, cyclohexanol, isooctyl alcohol, Guerbet alcohol, ethylene glycol monobutyl ether, and diethylene glycol butyl ether. In a preferred embodiment, the coupling agent is isopentyl glycol.

[0059] The dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, sodium citrate, disodium edetate, sodium gluconate, sodium glucoheptonate, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium acid pyrophosphate, and disodium dihydrogen pyrophosphate. In a preferred embodiment, the dispersant is sodium glucoheptonate. Sodium glucoheptonate has excellent dissolution and dispersion properties. When introduced into the polishing liquid, it can keep the oily lubricant in good dispersibility for a long time.

[0060] The present invention also provides a method for preparing a polycarbonate polishing liquid, comprising the following steps:

[0061] S001. Add coupling agent and dispersant to water and stir until the solution is clear and transparent;

[0062] S002. Slowly add the oil lubricant, the organic base and the surfactant to the mixed solution obtained in step S001, and stir until the solution changes from turbid and unstable to clear and transparent uniform;

[0063] S003. Slowly add silicon dioxide to the mixed solution obtained in step S002, and stir until the solution is uniform to obtain a milky white polishing solution.

[0064] The preparation method provided by the present invention is simple and efficient, and the equipment used in the preparation method is easy to deploy, and can be widely promoted in material processing, especially in the polymer engineering material production and processing industry.

[0065] The present invention also provides a polishing liquid performance test method, which is used to test the performance of the polycarbonate polishing liquid, comprising the following steps:

[0066] C001. Cut the formed polycarbonate material into test blocks suitable for laboratory polishing machines; the molding method can be injection molding, extrusion molding, high temperature pressing molding, casting molding, etc.

[0067] C002. Use sandpapers of 180 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh and 2500 mesh, and grind and polish the test block in succession using sandpapers from coarse to fine. The positive pressure of each grinding and polishing is 5N. Rinse the surface of the test block after each grinding and polishing.

[0068] C003. Prepare the polycarbonate polishing solution or a dilution containing the polycarbonate polishing solution;

[0069] C004. Place the polishing pad on the turntable of the polishing machine, drip the polishing liquid evenly on the polishing pad, and then place the test block polished with sandpaper to start polishing. The positive pressure between the test block and the polishing pad is 5N, the polishing pad speed is 400-500RPM, the test block speed is 0-150RPM, and the polishing time is 7-10min. During polishing, drip the polishing liquid continuously at the position where the polishing pad contacts the test block and is relatively close to the center. After polishing, rinse off the polishing liquid remaining on the surface with water.

[0070] C005. Observe the grinding and polishing conditions of the polished test block under a high-power optical microscope.

[0071] Furthermore, in the above step C001, the test block should not be prepared by thermoforming of polycarbonate powder. When the polycarbonate test block is prepared by thermoforming, holes will be generated inside the test block, which will reduce the structural strength of the test block and make it impossible to achieve a polishing effect.

[0072] In the above step C002, the positive pressure of each grinding and polishing pass is 5N, the sandpaper speed is 300RPM, the test block speed is 0-60RPM, and the grinding and polishing time is 1min.

[0073] Since the surface of the polycarbonate test block is very rough after being cut, and its roughness is much higher than the particle size of the silica abrasive, step C002 uses sandpaper to roughly polish the cut test block, which can reduce the roughness of the test block surface and make the roughness of the test block surface close to the roughness of the polycarbonate material surface before actual polishing production. Therefore, when testing the polishing performance of the polishing liquid, it is possible to avoid the test block from wearing out the polishing pad, and the test results obtained can also be close to the polishing effect under the polishing processing method in bulk production, and can effectively evaluate the processing effect of the polishing liquid.

[0074] In addition, in step C002, the test block is first polished with sandpaper of small mesh number and then post-polished with sandpaper of large mesh number, which can ensure the grinding and polishing efficiency while reducing the damage to the sandpaper.

[0075] Furthermore, in step C003, the polycarbonate polishing liquid can be used as a stock solution or diluted with water. When the polishing liquid is diluted with water, the mass ratio of the polycarbonate polishing liquid to water is 1:(1-3).

[0076] Further, in step C004, the polishing pad can be damping cloth, resistance cloth, polishing leather, polyurethane, wool felt, etc., which can be selected according to the actual situation of the production site. In addition, in step C004, the positive pressure between the test block and the polishing pad is as small as possible, the rotation speed of the polishing pad is as large as possible, and the polishing time is extended, so that the polishing effect of the polishing liquid in the laboratory polishing machine can reach the polishing effect of actual production. Therefore, in step C004, the positive pressure between the test block and the polishing pad is set to 5N, the polishing pad rotation speed is set to 400-500RPM, the test block rotation speed is set to 0-150RPM, and the polishing time is set to 7-10min.

[0077] Furthermore, in step C005, the optical microscope equipment that can be used includes a metallographic microscope, an ultra-depth microscope, a laser profiler, a white light interferometer, etc. When the ultra-depth microscope, a laser profiler, a white light interferometer, etc. are used to observe the polished surface of the test block, the surface roughness can be measured at the same time, and the formula of the polishing liquid can be adjusted based on the measured surface roughness. The surface roughness is preferably below 0.5um.

[0078] It can be seen that the present invention can reproduce the polishing effect of mass production site by rough grinding the polycarbonate test block and strictly controlling the positive pressure between the test block and the polishing pad, the polishing pad rotation speed and the polishing time when the laboratory polishing machine is working, so as to effectively evaluate the processing effect of the polishing liquid in production. The polishing performance test method of the polishing liquid provided by the present invention is simple to operate, can be performed using a variety of laboratory polishing machines and optical microscopes, and can intuitively evaluate the effect of the polishing liquid.

[0079] In order to further illustrate the polycarbonate polishing liquid, preparation method and polishing liquid performance testing method provided by the present invention, the following examples and comparative examples are provided.

[0080] Example 1

[0081] This embodiment provides a polycarbonate polishing liquid, which includes the following components calculated by mass percentage:

[0082] Silica sol 57.8%, water 26.7%, coupling agent 6%, oil lubricant 3%, surfactant 3%, organic base 2.5%, dispersant 1.0%;

[0083] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 75-90 nm, and the mass percentage of water in the silica sol is 55%.

[0084] The oily lubricant is composed of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is 1:2.

[0085] The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0086] This embodiment also provides a method for preparing a polycarbonate polishing liquid, comprising the following steps:

[0087] S001. Add 6% coupling agent and 1.0% dispersant to 26.7% (in the preparation method, all are mass percentages) of water and stir until the solution is clear and transparent;

[0088] S002. Slowly add 3% of an oily lubricant, 2.5% of an organic base and 3% of a surfactant to the mixed solution obtained in step S001, and stir until the solution changes from turbid and unstable to clear and transparent uniform;

[0089] S003. Slowly add 57.8% silica sol to the mixed solution obtained in step S002, and stir until the solution is uniform to obtain a milky white polishing solution.

[0090] This embodiment also provides a method for testing the performance of a polycarbonate polishing liquid, comprising the following steps:

[0091] C001. The formed polycarbonate material with a diameter of 30 mm is cut into a cylinder with a length of 25 mm;

[0092] C002. Use sandpapers of 180 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh and 2500 mesh to grind and polish the bottom surface of the polycarbonate cylinder in succession from coarse to fine sandpaper. The positive pressure of each grinding and polishing is 5N, the sandpaper speed is 300RPM, the speed of the polycarbonate cylinder is 0-60RPM, the grinding and polishing time is 1min, and the surface of the polycarbonate cylinder is rinsed clean after each grinding and polishing;

[0093] C003. Prepare the polycarbonate polishing liquid dilution, the mass ratio of polycarbonate polishing liquid to water is 1:1;

[0094] C004. Use a black damping cloth as a polishing pad, attach the polishing pad to the polishing machine turntable, evenly drip the polishing liquid on the polishing pad, and then place the polycarbonate cylinder polished with sandpaper to start polishing, wherein the positive pressure between the polycarbonate cylinder and the polishing pad is 5N, the polishing pad speed is 500RPM, the polycarbonate cylinder speed is 150RPM, and the polishing time is 10min; during polishing, continuously drip the polishing liquid at the position where the polishing pad contacts the polycarbonate cylinder and is relatively close to the center; after polishing, rinse off the polishing liquid remaining on the surface with water;

[0095] C005. Observe the polishing condition of the polished polycarbonate cylinder under a super depth of field microscope.

[0096] Comparative Example 1-1

[0097] This comparative example provides a polycarbonate polishing liquid, which comprises the following components by mass percentage:

[0098] Silica sol 57.8%, water 26.7%, coupling agent 6%, oil lubricant 3%, surfactant 3%, organic base 2.5%, dispersant 1.0%;

[0099] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 110-120 nm, and the mass percentage of water in the silica sol is 55%.

[0100] The oily lubricant is composed of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is 1:2.

[0101] The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0102] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0103] This comparative example also provides a performance testing method for a polycarbonate polishing liquid, which is the same as that in Example 1.

[0104] Comparative Example 1-2

[0105] This comparative example provides a polycarbonate polishing liquid, and the composition of the polishing liquid is the same as that of Example 1.

[0106] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0107] This comparative example also provides a method for testing the performance of a polycarbonate polishing liquid, which also includes steps C001, C002, C003, C004 and C005. Steps C001, C002, C003 and C005 are the same as those in Example 1. In step C004, the positive pressure between the polycarbonate cylinder and the polishing pad is 15N, and the rest is the same as in Example 1.

[0108] Comparative Examples 1-3

[0109] This comparative example provides a polycarbonate polishing liquid, which, calculated by mass percentage, comprises the following components:

[0110] Silica sol 57.8%, water 26.7%, coupling agent 6%, oil lubricant 3%, surfactant 3%, organic base 2.5%, dispersant 1.0%;

[0111] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 75-90 nm, and the mass percentage of water in the silica sol is 55%.

[0112] The oily lubricant only includes fatty acid methyl ester. The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0113] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0114] This comparative example also provides a performance testing method for a polycarbonate polishing liquid, which is the same as that in Example 1.

[0115] Example 2

[0116] This embodiment provides a polycarbonate polishing liquid, which includes the following components calculated by mass percentage:

[0117] Silica sol 48.9%, water 33.5%, oil lubricant 5%, surfactant 5%, coupling agent 4%, organic base 3%, dispersant 0.6%;

[0118] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 75-90 nm, and the mass percentage of water in the silica sol is 55%.

[0119] The oily lubricant is composed of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is 2:3.

[0120] The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0121] This embodiment also provides a method for preparing a polycarbonate polishing liquid, which is the same as that of Embodiment 1.

[0122] This embodiment also provides a performance testing method for a polycarbonate polishing liquid, which is the same as that in embodiment 1.

[0123] Comparative Example 2-1

[0124] This comparative example provides a polycarbonate polishing liquid, which comprises the following components by mass percentage:

[0125] Silica sol 48.9%, water 33.5%, oil lubricant 5%, surfactant 5%, coupling agent 4%, organic base 3%, dispersant 0.6%;

[0126] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 40-50 nm, and the mass percentage of water in the silica sol is 55%.

[0127] The oily lubricant is composed of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is 2:3.

[0128] The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0129] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0130] This comparative example also provides a performance testing method for a polycarbonate polishing liquid, which is the same as that in Example 1.

[0131] Comparative Example 2-2

[0132] This comparative example provides a polycarbonate polishing liquid, and the composition of the polishing liquid is the same as that of Example 2.

[0133] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0134] This comparative example also provides a performance test method for a polycarbonate polishing liquid, which also includes steps C001, C002, C003, C004 and C005. Steps C001, C002, C003 and C005 are the same as those in Example 1, and in step C004, the polishing time is 4 minutes, and the rest is the same as in Example 1.

[0135] Example 3

[0136] This embodiment provides a polycarbonate polishing liquid, which includes the following components calculated by mass percentage:

[0137] Silica sol 48.9%, water 35.6%, coupling agent 6%, oil lubricant 3%, surfactant 3%, organic base 2.5%, dispersant 1.0%;

[0138] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 75-90 nm, and the mass percentage of water in the silica sol is 55%.

[0139] The oily lubricant is composed of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is 1:2.

[0140] The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0141] This embodiment also provides a method for preparing a polycarbonate polishing liquid, which is the same as that of Embodiment 1.

[0142] This embodiment also provides a performance testing method for a polycarbonate polishing liquid, which is the same as that in embodiment 1.

[0143] Comparative Example 3-1

[0144] This comparative example provides a polycarbonate polishing liquid, which comprises the following components by mass percentage:

[0145] Silica sol 84.5%, coupling agent 6%, oil lubricant 3%, surfactant 3%, organic base 2.5%, dispersant 1.0%;

[0146] The solid content of the silica sol is 45%, the particle diameter of the silica sol in the silica sol is 75-90 nm, and the mass percentage of water in the silica sol is 55%.

[0147] The oily lubricant is composed of fatty acid methyl ester and neodecanoic acid, and the mass ratio of fatty acid methyl ester to neodecanoic acid is 1:2.

[0148] The organic base is diglycolamine. The surfactant is lauryl alcohol polyoxyethylene ether. The coupling agent is isopentyl glycol. The dispersant is sodium glucoheptonic acid.

[0149] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0150] This comparative example also provides a performance testing method for a polycarbonate polishing liquid, which is the same as that in Example 1.

[0151] Comparative Example 3-2

[0152] This comparative example provides a polycarbonate polishing liquid, and the composition of the polishing liquid is the same as that of Example 3.

[0153] This comparative example also provides a method for preparing a polycarbonate polishing liquid, which is the same as that in Example 1.

[0154] This comparative example also provides a performance test method for a polycarbonate polishing liquid, which also includes steps C001, C002, C003, C004 and C005. Steps C001, C003, C004 and C005 are the same as those in Example 1. In step C002, the mesh numbers of the sandpaper are 180 mesh, 400 mesh, 800 mesh and 2000 mesh, respectively, from low to high. The rest are the same as those in Example 1.

[0155] According to the polishing liquid (polishing) performance test method provided in Example 1, the polishing performance test of the polycarbonate polishing liquid provided in Example 1, Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3, Example 2, Comparative Example 2-1, Comparative Example 2-2, Example 3, Comparative Example 3-1, and Comparative Example 3-2 was performed. After the test, the polishing conditions of the polycarbonate materials in each example and comparative example under the ultra-depth of field microscope are shown in the following figure. Figures 3 to 12 shown.

[0156] in, Figure 3 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Example 1 (the brown lines are the effects of light photography, not defects on the surface of the material after polishing); Figure 4 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Comparative Example 1-1; Figure 5 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Comparative Example 1-2; Figure 6 The following are photos of the polycarbonate material in comparative example 1-3, which was polished under an ultra-depth-of-field microscope; Figure 7 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Example 2; Figure 8 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Comparative Example 2-1; Fig. 9 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Comparative Example 2-2; Fig.10This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Example 3; Fig.11 This is a photo of the polishing of the polycarbonate material under an ultra-depth-of-field microscope in Comparative Example 3-1; Fig.12 This is a photograph of the polycarbonate material in Comparative Example 3-2 being polished under an ultra-depth-of-field microscope.

[0157] See also Figures 3 to 6 ,Depend on Figure 3 It can be seen that after the polycarbonate material is polished with the polycarbonate polishing liquid provided in Example 1, the surface of the material is smooth without obvious wear marks and orange peel texture; while after the polycarbonate material is polished with the polycarbonate polishing liquid provided in Comparative Example 1-1, the surface of the material has obvious orange peel texture and a small amount of cross wear marks. This is because in the polishing liquid provided in Comparative Example 1-1, the silica particle diameter is 110-120nm. Compared with the silica particles with a particle diameter of 75-90nm, the silica particles are too coarse and will produce greater grinding and polishing force. At the same time, excessive pressure during the grinding and polishing process will also cause wear marks on the material surface.

[0158] After the polycarbonate material was polished using the polycarbonate polishing liquid provided in Comparative Example 1-2, there were fork-like wear marks on the surface of the material. This was because the positive pressure between the polycarbonate cylinder and the polishing pad was 15N during the test, and the test pressure was too high.

[0159] After the polycarbonate polishing liquid provided in Comparative Examples 1-3 polished the polycarbonate material, the material surface had both orange peel texture and wear marks. This is because when fatty acid methyl ester is used alone, the lubricating effect of the polishing liquid is insufficient. When polishing the polycarbonate material, over-polishing is likely to occur, which will cause new wear marks and orange peel on the surface of the polycarbonate material.

[0160] See also Figures 7 to 9 ,Depend on Figure 7 It can be seen that after the polycarbonate material is polished using the polycarbonate polishing liquid provided in Example 2, the surface of the material is smooth without obvious wear marks and orange peel texture; while after the polycarbonate material is polished using the polycarbonate polishing liquid provided in Comparative Example 2-1, the surface roughness of the material is high. This is because the diameter of the silica particles in the polycarbonate polishing liquid provided in Comparative Example 2-1 is relatively small, resulting in a small grinding and polishing force on the material.

[0161] After the polycarbonate material was polished using the polycarbonate polishing liquid provided in Comparative Example 2-2, the surface roughness of the material was high and there were wear marks. This was because the polishing time was too short during the test, resulting in insufficient grinding and polishing.

[0162] See also Figures 10 to 12 ,Depend on Fig.10It can be seen that after the polycarbonate material is polished with the polycarbonate polishing liquid provided in Example 2, the surface of the material is smooth without obvious wear marks and orange peel texture; while after the polycarbonate material is polished with the polycarbonate polishing liquid provided in Comparative Example 3-1, the surface of the material has obvious orange peel. This is because the amount of silicon dioxide (silica sol) added to the polycarbonate polishing liquid provided in Comparative Example 3-1 is too much, resulting in excessive pressure during the test, and orange peel texture appears on the surface of the material due to excessive heat generation.

[0163] After the polycarbonate material was polished using the polycarbonate polishing liquid provided in Comparative Example 3-2, there were obvious wear marks on the surface of the material. This is because the material surface was not fully polished when the polycarbonate test block was initially polished with sandpaper, resulting in high surface roughness of the material. When using a polishing machine, the polishing liquid could not effectively polish the material.

[0164] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A polycarbonate polishing liquid, characterized in that: Calculated by mass percentage, it includes the following components: Water 58.5-62.5%, silicon dioxide 22-26%, coupling agent 4-6%, oily lubricant 3-5%, surfactant 3-5%, organic base 2.5-3%, dispersant 0.5-1.0%; The particle diameter of the silicon dioxide is 75 to 90 nm.

2. The polycarbonate polishing liquid according to claim 1, characterized in that: The silicon dioxide is obtained from silica sol, and the silica sol comprises the following components: Silicon dioxide 45%, water 55%.

3. The polycarbonate polishing liquid according to claim 1, characterized in that: The oily lubricant includes at least one of fatty acid octyl ester, fatty acid isooctyl ester, oxidized fatty acid octyl ester, tall oil, fatty acid methyl ester, tall oil fatty acid, pentaerythritol oleate, cottonseed oil, tetrapolyricinoleate, neodecanoic acid, and trimethylolpropane oleate.

4. The polycarbonate polishing liquid according to claim 1, characterized in that: The organic base includes at least one of monoethanolamine, diethanolamine, triethanolamine, diglycolamine, tricyclohexylamine, dimethylamine, diethylamine, aniline and tetrahydroxymethylamine.

5. The polycarbonate polishing liquid according to claim 1, characterized in that: The surfactant includes at least one of lauramide propylamine oxide, tallow amine polyoxyethylene ether, oleylamine polyoxyethylene ether, dodecylamine polyoxyethylene ether, lauryl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, oleic acid polyoxyethylene ether and Tween-80.

6. The polycarbonate polishing liquid according to claim 1, characterized in that: The coupling agent includes at least one of ethanol, ethylene glycol, isopropanol, diethylene glycol, isopentyl glycol, cyclohexanol, isooctyl alcohol, Guerbet alcohol, ethylene glycol monobutyl ether, and diethylene glycol butyl ether.

7. The polycarbonate polishing liquid according to claim 1, characterized in that: The dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, sodium citrate, disodium edetate, sodium gluconate, sodium glucoheptonic acid, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium acid pyrophosphate, and disodium dihydrogen pyrophosphate.

8. A method for preparing a polycarbonate polishing liquid as claimed in any one of claims 1 to 7, comprising the following steps: S001. Add coupling agent and dispersant to water and stir until the solution is clear and transparent; S002. Slowly add the oil lubricant, the organic base and the surfactant to the mixed solution obtained in step S001, and stir until the solution changes from turbid and unstable to clear and transparent uniform; S003. Slowly add silicon dioxide to the mixed solution obtained in step S002, and stir until the solution is uniform to obtain a milky white polishing solution.

9. A method for testing the performance of a polishing liquid, characterized in that: Used to perform performance testing on the polycarbonate polishing liquid according to any one of claims 1 to 7, comprising the following steps: C001. Cut the formed polycarbonate material into test pieces suitable for laboratory polishing machines; C002. Use sandpapers of 180 mesh, 400 mesh, 800 mesh, 1200 mesh, 2000 mesh and 2500 mesh, and grind and polish the test block in succession from coarse to fine sandpaper. Rinse the surface of the test block after each grinding and polishing. C003. Prepare the polycarbonate polishing solution or a dilution containing the polycarbonate polishing solution; C004. Place the polishing pad on the turntable of the polishing machine, drip the polishing liquid evenly on the polishing pad, and then place the test block polished with sandpaper to start polishing. The positive pressure between the test block and the polishing pad is 5N, the polishing pad speed is 400-500RPM, the test block speed is 0-150RPM, and the polishing time is 7-10min. During polishing, drip the polishing liquid continuously at the position where the polishing pad contacts the test block and is relatively close to the center. After polishing, rinse off the polishing liquid remaining on the surface with water. C005. Observe the grinding and polishing conditions of the polished test block under a high-power optical microscope.

10. The polishing liquid performance testing method according to claim 9, characterized in that: In step C003, the diluent of the polycarbonate polishing liquid includes polycarbonate polishing liquid and water, and the mass ratio of the polycarbonate polishing liquid to water is 1:(1-3).

Citation Information

Patent Citations

  • Polishing fluid for aviation plexiglass and its preparation method

    CN115305012B